Prinsip pustakawan dalam seleksi bahan pustaka di Perpustakaan Sekolah Menengah Kejuruan 1 Pacitan - Ardhina Pratiwi Pratiwi (Universitas Padjadjaran, 2018)
Selection of library materials is an important activity which aims to determine the selection of library materials based on characteristics and needs of users. Library selection activities are conducted by professional librarians who have the ability to develop collections. Due to the importance of library materials selection activities, the researcher conducted a study at the Sekolah Menengah Kejuruan 1 Pacitan Library. This study aimed to describe the principles of the librarian in the library material selection process at the library of Sekolah Menengah Kejuruan 1 Pacitan. The study used the descriptive qualitative method, with sampling using the purposive sampling technique to the librarian and non-librarian at the Sekolah Menengah Kejuruan 1 Pacitan Library. The data collection technique in this study used the semi-structured interview instruments. The researcher used the scope of library material selection principles consisting of the traditionalist, liberal and pluralistic view. According to the liberal view; the study results showed that librarians were not able to market the library through the approach to students. To the traditionalist view, the main principle in meeting the needs of students was based on the quality of library materials. While the pluralistic view suggested that most students were not satisfied with the literature available at the Sekolah Menengah Kejuruan 1 Pacitan Library. Based on that, the Sekolah Menengah Kejuruan 1 Pacitan Library has applied the traditionalist principles which can be seen from the quality of library materials that will be accessible to the students.